Mechanistic Insights into Crystal Violet Degradation by Peroxymonocarbonate-Based Oxidation Systems - Tinh, Vu Thi; Duy, Vu Ngoc; Viet, Nguyen Thi Bich (VNU Journal of Science: Natural Sciences and Technology, 2025)
In this study, peroxymonocarbonate (PMC), formed directly from the reaction between H 2 O 2 and HCO 3 ‒ , was applied to decolorize Crystal Violet (CV), a widely used dye in the textile industry. Experimental results showed that PMC can decolorize CV almost completely in 30 minutes, superior to the H 2 O 2 or H 2 O 2 /Co 2+ systems. The effects of reactant concentration, catalyst, pH, co-existing anions, and UV irradiation were systematically investigated and optimized. The results showed that at concentrations of 8 mM HCO 3 ⁻, 20 mM H 2 O 2 , 1.7 µM Co 2 ⁺, and pH 8.5 (inherent pH), under UV irradiation, the PMC system can completely mineralize organic substances and is not affected by anions. Experiments using ROS scavengers showed that the oxidizing agents generated in the PMC system play an important role in CV decolorization, in which the superoxide radical (O 2 • ⁻) contributes more to the CV decolorization process compared to the carbonate radical (CO 3 • ⁻), while the hydroxyl radical ( • OH) and singlet oxygen ( 1 O 2 ) are almost negligible.